Belt and Road : The First Decade. - Rogelja, Igor (Agenda Publishing, 2022)
China's Belt and Road Initiative (BRI) is one of the most talked about and little understood policy initiatives of China. This short book offers a comprehensive, balanced and policy-oriented analysis of the BRI and what it means for western businesses and polities.
Description based upon print version of record.
Keywords: Yi dai yi lu (Initiative : China); Nouvelles routes de la soie.; China -- Economic policy -- 2000-; Chine -- Politique économique -- 2000-; Economic policy; China; Since 2000